Test of Number of Knife Edge on Mechanical Cassava Slicer - Dedi R.Pranata Barus; Ainun Rohana; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was done to test effect of number of knife edge on the effective  capacity of the equipment,  percentage of material left in the equipment, and percentage of material that was sliced completely. This research was using completely randomized design non factorial. It was found that the effective capacity of the equipment, percentage of material was sliced completely, on one knife edge 45.82 kg hr-1, 3.59%, 3.45%, on two knife edge 49.70 kg hr-1, 4.07%, 4.11%, on three knife edge 68.58 kg hr-1, 10.10%, 4.72%. Respectively the results showed  that number of knife edge had zig, don’t effect on the  effective capacity and  percentage of material left in the equipment, and had no effect on the percentage of material that was sliced completely. Key words : Knife edge, slicer, cassava